Valuable but Flawed: Stakeholder Perceptions of the Ontario Mandatory Community Involvement Program - Barbara Harrison (University of Windsor, 2012)
The purpose of this study was to explore the experiences of five groups of people-students, parents, community organization representatives, guidance counsellors, and principals-in dealing with a community involvement requirement for secondary school graduation in Ontario. Ten people were interviewed, resulting in insights as to what makes the program work for the various groups, and suggestions for improvement. Interviewee recommendations include creating a more structured program to increase the consistency of program implementation, reducing the administrative burden on schools, increasing the number of required hours, and having more support for the program from the Ontario government and the Ontario Ministry of Education.